(untitled) (Itinera, 2017)
Since the second half of the XX Century, the attention to the food intended as a component of daily rituals increased within art practices, especially within performance art and the making of complex art installations. Food appears to be a central element for the design of spaces and objects, a practice that constantly dialogues with the cultural context, for which it advances also solutions and interpretations in virtue of its spatial and visual metaphors of the relationship between humans and food. This paper presents significant examples starting from the Modern era â in which, with the advent of the merchandise, the sense of loss within a new universe of objects, images and sounds emerges â and arriving at the crisis of this perspective in which a comparison with artistic practices becomes promising.Â